SINGLE-INCISION LAPAROSCOPY VERSUS STANDARD LAPAROSCOPY FOR COLORECTAL SURGERY : A SYSTEMATIC REVIEW - Tommy Antariksa , Sulistyo Negoro (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Colorectal cancer (CRC) is the third most prevalent malignancy worldwide. Only surgical resection is curative for colorectal cancer. Recent advances in surgical techniques, such as robot-assisted laparoscopic surgery (RALS), single-incision laparoscopic surgery (SILS), and natural orifice transluminal endoscopic surgery (NOTES), etc., have benefited colorectal cancer patients tremendously. The aim: This study aims to compare single-incision laparoscopy and conventional laparoscopy for colorectal surgery. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 201 articles, whereas the results of our search on SagePub brought up 119 articles. The results of the search conducted for the last year of 2013 yielded a total 54 articles for PubMed and 23 articles for SagePub. In the end, we compiled a total of 16 papers, 11 of which came from PubMed and 5 of which came from SagePub. We included six research that met the criteria. Conclusion: Previous studies have consistently shown that complications within 30 days postoperatively and incision size in patients with single port are better than patients with multiport. Perioperative outcome and long-term survival rates were similar between the two groups.